Acute lymphoblastic leukemia - Toljić, Branka; Stojanovic-Ristic, Snezana (General Practice, 2023)
Introduction. Acute lymphoblastic leukemia (ALL) is a heterogeneous disease distinguished by clonal replication and piling of immature lymphoid cells in the bone marrow and lymph organs. The etiology is unknown but radiation and some chemical exposure, as well as genetics, might play a role. The disease onset is abrupt. Clinical presentation is characterized by a variety of general symptoms: fatigue, malaise, night sweats, weight loss, fever. The diagnosis is based on a patient`s history, physical examination, blood tests, bone marrow biopsy, cytogenetic, and immunohistochemical tests. Core treatments are poly-chemotherapy, radiation therapy, hematopoietic stem cell transplantation.Case report. We presented a 20-year-old patient. On his first visit, he complained of neck pain. He was treated by a physiotherapist. After he finished with physical therapy we noticed pancytopenia in his lab work. His general practitioner (GP) referred him to a hematologist where further medical examinations were performed and ALL diagnosis was made. The treatment started with a chemotherapy regimen. An allogeneic hematopoietic stem cell transplantation was performed afterward. In the follow-up, regular haematologic assessments were done, as well as, the assessment of MRD (Minimal Residual Disease). Complete morphologic remission was maintained the whole time but with positive MRD findings. He received an antiCD22 monoclonal antibody therapy and the therapeutic response was good. Eight months later B-ALL relapse was confirmed. The patient`s general condition got worse and in spite of an intensive therapy the patient died.Conclusion. Acute lymphoblastic leukemia is a disease whose outcome depends on many a factor. Due to atypical symptoms, it should be taken into consideration to shorten the time to diagnosis, provide timely treatment and thus influence the disease outcome.
Keywords: leukemia; young person; early diagnosis